Activation and Photoinduced Release of Alkynes on a Biomimetic Tungsten Center: The Photochemical Behavior of the W−S‐Phoz System - Peschel, Lydia M. (Chemistry, 2019)
The synthesis and structural determination of four tungsten alkyne complexes coordinated by the bio‐inspired S,N‐donor ligand 2‐(4′,4′‐dimethyloxazoline‐2′‐yl)thiophenolate (S‐Phoz) is presented. A previously established protocol that involved the reaction of the respective alkyne with the bis‐carbonyl precursor [W(CO)(2)(S‐Phoz)(2)] was used for the complexes [W(CO)(C(2)R(2))(S‐Phoz)(2)] (R=H, 1 a; Me, 1 b; Ph, 1 c). Oxidation with pyridine‐N‐oxide gave the corresponding W‐oxo species [WO(C(2)R(2))(S‐Phoz)(2)] (R=H, 2 a; Me, 2 b; Ph, 2 c). All W‐oxo‐alkyne complexes (2 a, b, c) were found to be capable of alkyne release upon light irradiation to afford five‐coordinate [WO(S‐Phoz)(2)] (3). The photoinduced release of the alkyne ligand was studied in detail by in situ (1)H NMR measurements, which revealed correlation of the photodissociation rate constant (2 b>2 a>2 c) with the elongation of the alkyne C≡C bond in the molecular structures. Oxidation of [WO(S‐Phoz)(2)] (3) with pyridine‐N‐oxide yielded [WO(2)(S‐Phoz)(2)] (4), which shows highly fluxional behavior in solution. Variable‐temperature (1)H NMR spectroscopy revealed three isomeric forms with respect to the ligand arrangement versus each other. Furthermore, compound 4 rearranges to tetranuclear oxo compound [W(4)O(4)(μ‐O)(6)(S‐Phoz)(4)] (5) and dinuclear [{WO(μ‐O)(S‐Phoz)}(2)] (6) over time. The latter two were identified by single‐crystal X‐ray diffraction analyses.